DUKUNGAN SOSIAL PENGASUH DALAM MENINGKATKAN PENYESUAIAN SOSIAL REMAJA - Oskia, Umi; Wibowo, Agus; Mudaim, Mudaim (Counseling Milenial (CM), 2023)
The purpose of this study was to determine emotional support, appreciation support, instrumental support and informative support in improving Adolescent Social Adjustment at the MetroBudi Utomo Muhammadiyah Orphanage. This type of research is descriptive qualitative. The data subjects in this study were Orphanage Caregivers and Foster Children. Data obtained through interview and observation methods. Data analysis uses the miles model, namely data collection, data reduction, data presentation, and drawing conclusions. Validity testing can be done by means of triangulation of sources. The conclusions in this study are (1) emotional support of caregivers in improving the social adjustment of adolescents at the Metro Budi Utomo Muhammadiyah Orphanage, namely by having a close relationship between caregivers and foster children, having sympathy and empathy and having a sense of concern. (2) the support of awards given by caregivers such as encouragement in the form of appreciation awards and motivation so that foster children are more enthusiastic in carrying out all their activities. (3) instrumental support provided by caregivers, namely assistance involving other people in the form of assistance and provision of facilities such as clothing, food and shelter. (4) informative support of caregivers in guiding or providing direction in the form of mental and spiritual development activities and instructions in solving problems experienced by foster children.